A Cucurbit[7]uril Based Molecular Shuttle Encoded by Visible Room‐Temperature Phosphorescence. Issue 12 (24th November 2015) - Gong, Yifan; Chen, Hui; Ma, Xiang; Tian, He
Abstract: A visible room‐temperature phosphorescence (RTP) signal, generated by complexation of cururbit[7]uril (CB[7]) and bromo‐substituted isoquinoline in aqueous solution, is employed to address the shuttling of a pH‐controlling molecular shuttle fabricated by CB[7] and a phosphor 6‐bromoisoquinoline derivativeIQC[5] . The CB[7] host shuttles along the axial guest under acidic conditions, accompanied by a weak RTP emission signal, while deprotonation of the guestIQC[5] makes the CB[7] wheel locate on the phosphor group, leading to intense RTP emission. The switching RTP emission of the molecular shuttle, via pH adjusting, can be visibly identified by the naked eye. This is the first CB‐based molecular shuttle with an RTP signal as the output address of its shuttling and conformation. Abstract : A sensitive shuttle : A cucurbit[7]uril‐based molecular shuttle with pH‐sensitive room‐temperature phosphorescence emission identified by the naked eye is reported.